Knowledge construction in the classroom: a meaningful pedagogical dialogue - Jesuína Lopes de Almeida Pacca (Investigações em Ensino de Ciências, 2015)
Teacher’s performance at their real classroom was analyzed in regard to the applied pedagogical interaction. These teachers were participating in a long range continuous formation course that uses the strategy of analyzing pedagogical planning while it was being elaborated , applied and continuously evaluated by the teacher; the course aimed to the construction of professional competence with an adequate sight of the classroom interaction, within constructivist parameters. The teacher pedagogical planning was the study object: it was discussed continuously by the peers group and the coordinator who intended to point out to the explicit pedagogical content and to the content objectives that were declared for every class plan. The learning objectives and the procedures contained within it were confronted with the real evidence of learning. In these discussions learning concepts that were coherent with constructivism were invoked in addition to science contents and their nature. Dialogue was important in these discussions and stressed as a means for teaching and continuous evaluation. In this dynamical process, the teacher planning was being constantly redrafted, changing the adjustment of that classroom students to the planned knowledge acquisition. This course dynamics, led by the coordinator, intended to be reproduced by participants with their students, at least in part. We noticed surprising results in these teachers professional development besides those that were concretely planned: the transference of the course procedures to the classroom seems to happen in regard to the presence of dialogue but the most meaningful part was individual and particular progress that was included in the development of their classes and led to an improvement of abilities. We concluded that unexpected results can be converted into poles of professional performance growth and performance evolution . These results have led us to give special importance to the setting up and maintenance of a dialogue the we have called significant pedagogical dialogue in the interaction that must happen in a teaching situation.